Semipolar GaN(10–11) Epitaxial Layer Prepared on Nano‐Patterned SiC/Si(100) Template. Issue 2 (26th September 2018) - Bessolov, Vasily; Zubkova, Anna; Konenkova, Elena; Konenkov, Steven; Kukushkin, Sergey; Orlova, Tatiana; Rodin, Sergey; Rubets, Vladimir; Kibalov, Dmitry; Smirnov, Valery
Abstract : A new approach is proposed to the synthesis of a semipolar GaN on a Si(100) substrate at the surface of which the V‐shaped nanostructures with the characteristic size of elements as low as 100 nm are formed. It has been demonstrated that application of buffer layers of 3C‐SiC and AlN enables formation of the GaN(10–11) layer characterized by the full width at half maximum value as low as ωθ ≈45 arcmin for the X‐ray diffraction rocking curve. The model based on anisotropic nucleation of AlN on the V‐shaped nanostructure is proposed to explain the growth of the GaN layer in a single semipolar direction. Abstract : In this article, Bessolov et al. focus on the growth of the GaN layer in a semipolar direction by heteroepitaxy of the GaN layer on nano‐patterned Si(100) substrate with V‐shaped nano‐grooves arranged with the period as low as 100 nm, combined with the synthesis of a nano‐sized SiC layer formed by solid‐phase substitution of silicon atoms by carbon atoms.